Komunikasi Dialogis dalam Rangka Penyelesaian Konflik antara Pelaku Industri Dengan Masyarakat - Sabiati; Hastjarjo, Sri; Sudarmo (Procedia of Social Sciences and Humanities, 2022)
Multi-group conflict occurs when community groups with different interests from other groups have a variety of priorities for each resource and the development of management policies. Likewise in the dynamics of conflict between industry players and the community in defending their every interest. Conflict complexity basically includes various combinations of power, value and economic resources. Related to complexity which is often beyond the authority of institutions in general and there are standard procedures that have been carried out so far, to build consensus from various stakeholders, it is necessary to have a resolution by conducting a collaborative approach involving various other constituents. This collaborative approach in groups needs to be carried out dialogically in order to get an understanding between the conflicting groups. Then, among others, they reach consensus to achieve the desired resolution between the interests of stakeholders.